Tribal intolerance and its relationship to the tendency to violence among students of Mu’tah University - Al-frehat, Basem Mohammed; Hameed Aljbour, Rami Abed Al (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the level of tribal intolerance and its relationship to the tendency to violence among students of Mutah University, study sample consisted of (200) students from the Faculty of Education at Mutah University, the questionnaire was used as a tool for study, and the results showed that the level of tribal intolerance and the level of tendency to violence among Mutah University students came with intermediate degrees and mathematics (2.91) and (2.63), respectively,The results showed that there are statistically significant differences in the level of tribal intolerance according to the variables of the cumulative average and the place of residence, and the presence of statistically significant differences in the level of tendency to violence according to the variable of the cumulative average, and the results also indicated a positive relationship between the level of tribal intolerance and the tendency to violence among university students Mutah, and based on the results, a number of recommendations were formulated.